MENTAL HEALTH AMONG UNIVERSITY STUDENTS: EXAMINING DEPRESSION, ANXIETY, PANIC ATTACKS, AND TREATMENT-SEEKING BEHAVIOUR - Dr. Prasanna Deshpande (IJRDO - Journal of Social Science and Humanities Research, 2026)
University students are more likely to suffer from mental health disorders that impair their academic success and emotional health and quality of life. This study aimed to explore the prevalence of depression, anxiety, panic attacks and treatment-seeking behavior among university students in Malaysia, which was conducted using the secondary data of 101 respondents from International Islamic University, Malaysia. The quantitative cross-sectional design was used and descriptive statistics, Chi-square, and Fisher’s exact test were used to explore associations and binary logistic regression was used to explore predictors of treatment-seeking behaviour. The results indicated that 63.4% of students had at least one mental health disorder, with 34.7% of students feeling depressed, 33.7% of students feeling anxious, and 32.7% of students having a panic attack. There was a significant association between marital status and depression and panic attack, while gender, year of study and CGPA did not have significant association. Even with this high rate of psychological distress, only 5.9% of those involved in the study sought professional help, with depression being the most significant predictor of help-seeking. The results underscore the pressing need for holistic university mental health programs, screening measures, efforts to reduce stigma, and the provision of counselling services to ensure timely interventions and enhance student mental health.